On the Critique of Ivan Szelenyi’s Reception of Max Weber’s Sociology of Rule – with an Excurse on Weber’s Stay in Vienna - Treiber, Hubert (SocietàMutamentoPolitica, 2023)
The article critically examines Ivan Szelenyi’s reception of Max Weber’s sociology of rule, which he did in his essay under the title «Weber’s theory of domination and post-communist capitalism» in Theory & Society 2016, 45 (1): 1-24. The criticism exclusively concerns Ivan Szelenyi’s rendering of Weber’s sociology of rule, for example his comments on Weber’s concepts of power and domination. I refer directly to passages in Szelenyi where he deviates incorrectly from Weber’s sociology of rule (such as in his depiction of power and domination according to Weber). Even someone who is not familiar with Szelenyi’s text will benefit from my criticism insofar as it presents a correct, comprehensive account of Weber’s sociology of rule with its central concepts.